Assessing benefits and risks of incorporating plastic waste in construction materials - Cirino, Erica; Curtis, Sandra; Wallis, Janette; Thys, Tierney; Brown, James; Rolsky, Charles; Erdle, Lisa M. (Frontiers in Built Environment, 2023)
Plastic pollution and climate change are serious and interconnected threats to public and planetary health, as well as major drivers of social injustice globally. Prolific use of plastics in the construction industry is a key contributor to these crises. Businesses, materials scientists, institutions, and other interested stakeholders are currently exploring the incorporation of plastic waste into building materials and infrastructure at an accelerated rate. Examples include composite asphalt-plastic roads, plastic-concrete, plastic/crumb rubber turf, plastic lumber, plastic adhesives, and plastic soil stabilizers. While some believe this to be a reasonable end-of-life scenario for plastic waste, research shows such efforts may cause further problems. Focus on these uses of plastic waste represent an ongoing effort at “greenwashing,” which both delays and distracts from finding real solutions to the plastic pollution crisis. This mini review of existing research on the incorporation of plastic waste into building materials and infrastructure provides evidence that such practices exacerbate the negative health, social, and ecological impacts of plastics and increase demand for continued production of new (virgin) plastics. We urge caution — and more research — before widely adopting these practices. This review compares known impacts of these and various other treatments of plastic waste with recommendations for future research.